2021
DOI: 10.1111/jpn.13503
|View full text |Cite
|
Sign up to set email alerts
|

The effect of urine acidification on calcium oxalate relative supersaturation in cats

Abstract: Over the past 35 years, there has been a shift in the mineral composition of uroliths diagnosed in cats. Reports from the 1980s describe the majority of uroliths being composed of magnesium ammonium phosphate (MAP, or struvite) (Cannon et al., 2007;Houston & Moore, 2009;Osborne et al., 2009). However, in the mid-1990s, MAP only represented a third of submitted uroliths, and the vast majority was analyses as calcium oxalate (CaOx). The decrease in MAP uroliths seemed mirrored by the increase in CaOx, with uroli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…Alternatively, it was previously reported that older cats have a significantly lower urine pH and a higher potential to form CaOx crystals compared to younger cats [ 10 ]. However, a recent study showed that the risk of CaOx was not increased only with changes in urine pH [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, it was previously reported that older cats have a significantly lower urine pH and a higher potential to form CaOx crystals compared to younger cats [ 10 ]. However, a recent study showed that the risk of CaOx was not increased only with changes in urine pH [ 25 ].…”
Section: Discussionmentioning
confidence: 99%